Designing a model to empower the educational system performance of agricultural vocational schools - Samaneh Pazoki; Sabouri, Mohammad Sadegh; Elham Danaee; Ahmad Reza Ommani (Journal of Technical Education and Training, 2022)
This research aimed to compare the perspective of trainers and trainees at agricultural vocational schools in Iran regarding the empowerment of the educational system. It is an applied study in orientation, a hypothesis-testing study in goal, and a comparative causal study in strategy. Data were collected with a researcher-made questionnaire. The statistical population was composed of all trainers and trainees of the agricultural vocational schools in the 2020-2021 educational year amounting to 1119 trainees and 120 trainers, out of whom 169 trainees were sampled by simple randomisation and 120 trainers were sampled by the consensus method to participate in the research. The data were analysed in the Smart PLS3 and SPSS version 23 software packages. In addition to the descriptive statistics, the construct validity and the fit of the model were determined by confirmatory factor analysis and structural equation modelling. The management process, the educational process, curriculum content, technical teacher training, and the supply of space, equipment, and technology have positive and significant effects on the empowerment of the educational system at the agricultural vocational schools in both the trainers’ and trainees’ groups. The empowerment of the educational system at agricultural vocational schools is effective in achieving quality assurance in the educational system and subsequently, improving its quality continuously. This paper contributes to developing a theoretical framework by considering the dimensions and components underpinning an empowering educational system. This study is the first attempt to compare the perspective of trainers and trainees about an empowering educational system in agricultural vocational schools. The study provides a framework in which special attention is paid to the empowerment of the educational system at these schools so that the managers and trainers can work with more authority and play a role in improving the educational system of the agricultural vocational schools.